(untitled) (Nigerian Journal of Technology, 2021)
Radiation forecast is the milestone of the solar energy industry, making possible the existence of the whole market. Solar radiation models allow scientists and engineers to predict the behaviour of a PV system to perform technical and economic analysis. Despite the existence of numerous models, most of them are highly complex or require massive amounts of data, limiting solar energy start-ups. As a result, a state-of-the-art review was performed and based on it this study proposed a simple model that allows emerging solar companies to create preliminary analysis for their clients. The proposed model calculates the instant power of the envelope curve of PV generation, based on the Gaussian bell equation, by using the daily specific energy and a deviation proportional to the sun hours of the geographical information as parameters. With accurate meteorological data, results showed an acceptable performance, with a more straightforward implementation, when compared against those reported in the literature. http://dx.doi.org/10.4314/njt.v40i1.7